Assesing geodiversity in Tierra Del Fuego (Southern Patagonia, Argentina): A strategy to promote geotourism - Coronato, Andrea Maria Josefa (2020)
This contribution aims to present three hierarchized areas in central and northern Tierra del Fuego (Argentina) whose geodiversity may be used for educational purposes to encourage the Earth Sciences and to design of geotourism strategies. In comparison with south Tierra del Fuego, tourism development in both areas is still low. After applying a specific methodology, 163 georesources were identified, described, mapped and classified.